LC-MS/MS analysis and evaluation of the anti-inflammatory activity of components from BushenHuoxue decoction. (1st January 2017) - Sun, Dongdong; Yan, Qiuying; Xu, Xiaofang; Shen, Weixing; Xu, Changliang; Tan, Jiani; Zhang, Haibin; Li, Liu; Cheng, Haibo
Abstract: Context: BushenHuoxue decoction (BSHXD) is a Chinese medicine prescription, which is composed of nine Chinese medical materials, used to treat osteoarthritis (OA). Objective: This study develops sensitive and convenient LC-MS/MS methods to analyze chemical components from BSHXD, and assess the anti-inflammatory activities thereof. Materials and methods: The chemical composition from BSHXD water extract was qualitative analyzed by high-performance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (HPLC-ESI-Q-TOF-MS). Twelve reference compounds were analyzed by UPLC-ESI-MS/MS. Anti-inflammatory activities of target components were assessed by ELISA at 20 and 100 μg/mL. Results: It is the first time that 88 compounds were qualitatively identified from BSHXD, of which 12 with potential in treating OA according to the literature were quantified. Within BSHXD the contents of quercetin, isopsoralen, icarisideII, osthole, and isoimperatorin increased remarkably compared with those in single herb which make up BSHXD, the contents were 0.1999, 0.4634, 0.0928, 0.5364, and 0.1487 mg/g. ELISA data displayed that BSHXD and the five compounds mentioned inhibited the expressions of TNF-α, IL-6 and NO released from LPS-stimulated RAW264.7 cell, with maximum inhibition rates of 104.05% (osthole, 100 μg/mL), 100.03% (osthole, 100 μg/mL), and 93.46% (isopsoralen, 20 μg/mL), respectively. Discussion and conclusion: Content changes of 12 compounds in BSHXD and single herbs which comprise the prescription were measured and analyzed. Contents of five compounds increased may be explained by solubilization between drugs and chemical reaction. ELISA results reported that the increased contents of the five compounds could inhibit expression of the inflammatory factors.